2009
DOI: 10.1177/0892705708103403
|View full text |Cite
|
Sign up to set email alerts
|

Full-width Disbonding Effect on Repaired Cracks in Structural Panels with Bonded Composite Patches

Abstract: The process of repair of structures by using bonded composite patch is an effective and economical method to increase the service life of damaged structures. In this study, the finite element method is used to analyze the behavior of a crack repaired by a circular patch by computing the stress intensity factor (SIF) at the crack tip with and without the disbond. The obtained results show that the boron/epoxy 0° fiber perpendicular to the crack, considerably influences the reduction of the SIF with regard to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This could be explained by the higher rigidity in the loading direction of 1-ply Kevlar-49/epoxy material, which shares more than half of the load from the plate, thereby retarding the crack growth. This agrees with the speculation by Ouinas and Hebbar [21]. Moreover, reduction of SIF is also related to a smaller crack mouth opening displacement.…”
Section: Effect Of Patch Repairsupporting
confidence: 81%
See 1 more Smart Citation
“…This could be explained by the higher rigidity in the loading direction of 1-ply Kevlar-49/epoxy material, which shares more than half of the load from the plate, thereby retarding the crack growth. This agrees with the speculation by Ouinas and Hebbar [21]. Moreover, reduction of SIF is also related to a smaller crack mouth opening displacement.…”
Section: Effect Of Patch Repairsupporting
confidence: 81%
“…In general crack becomes unstable when its length exceeds certain limit [21]. To understand the role of crack length on the stress field of the plate, various crack length as 9%, 15%, 19%, 29%, 39%, and 49% of the plate width (w) were investigated.…”
Section: Effect Of Crack Lengthmentioning
confidence: 99%
“…It has been one of the most prevalent numerical tools in the field of fracture mechanics since the early 1960s. Researchers have been developing new techniques to improve the accuracy of FEM in application to fracture mechanics [3][4][5][6][7][8][9][10][11]. The use of quarter point elements in improving the accuracy of the solution around the crack tip was suggested by Henshel and Shaw [12] and Barsoum [13].…”
Section: Introductionmentioning
confidence: 99%
“…Most of computational models of the composite-patch-repaired plates utilized a simplified two-dimensional model [3,4,8,14]. However a plate under in-plane loading would develop highly complicated three-dimensional stresses if patches are bonded to its surfaces regardless of single or double sided patch.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have used the finite element method (FEM) in the calculation of the SIF in the case of strengthened cracks. 1317 All authors have shown that, after repair, the SIF presented an asymptotic behavior with regard to the crack length. This behavior is due to the fact that there is a transfer from the stresses in the cracked aluminum plate toward the composite patch through the adhesive layer.…”
Section: Introductionmentioning
confidence: 99%